General anesthesia, surgery and hospitalization in children and their effects upon cognitive, academic, emotional and sociobehavioral development: a review - J. C. S. Caldas (2004)
We reviewed current knowledge about cumulative and differential consequences of general anesthesia, surgery and hospitalization upon cognitive, academic, emotional and sociobehavioral development in children. Our strategy was to search the databases Pub Med and PsycINFO for all articles published between 1990 and May 2002. Based on the abstracts, we included all articles that related in any way to our subject of interest. Analysis of the articles showed preoperative anxiety as the main contributing factor to perioperative negative developmental effects. These were generally limited in duration and reversible. Research in this area tries to investigate predictors of increased anxiety, as well as the efficacy of different interventional programs for reduction of preoperative anxiety. We found no studies attempting to differentiate the relative influences of 'anesthetic stress', 'surgical stress' and 'hospitalization stress' on 'negative outcomes', 'areas of development affected' or 'duration of effects'. There are very few studies on academic and cognitive consequences. There is a need for more research in this area to provide useful guidelines for clinicians, to identify risk situations and to prevent negative outcomes.